Plant factories; crop transpiration and energy balance. (May 2017) - Graamans, Luuk; van den Dobbelsteen, Andy; Meinen, Esther; Stanghellini, Cecilia
Abstract: Population growth and rapid urbanisation may result in a shortage of food supplies for cities in the foreseeable future. Research on closed plant production systems, such as plant factories, has attempted to offer perspectives for robust (urban) agricultural systems. Insight into the explicit role of plant processes in the total energy balance of these production systems is required to determine their potential. We describe a crop transpiration model that is able to determine the relation between sensible and latent heat exchange, as well as the corresponding vapour flux for the production of lettuce in closed systems. Subsequently, this model is validated for the effect of photosynthetic photon flux, cultivation area cover and air humidity on lettuce transpiration, using literature research and experiments. Results demonstrate that the transpiration rate was accurately simulated for the aforementioned effects. Thereafter we quantify and discuss the energy productivity of a standardised plant factory and illustrate the importance of transpiration as a design parameter for climatisation. Our model can provide a greater insight into the energetic expenditure and performance of closed systems. Consequently, it can provide a starting point for determining the viability and optimisation of plant factories. Highlights: The energetic fluxes and crop transpiration are important in assessing the potential of plant factories The Penman-Monteith crop transpiration method can be used to accurately estimate energetic fluxes and crop transpiration This model is versatile enough to be applied to different crops, types of growing environment and interior climates The latent heat flux constitutes the largest single flow of energy and can even exceed the input energy (illumination) The energy demand of plant factories only exceeds that of Dutch greenhouses as a result of the need for artificial lighting